Cesarean section on request - moral problem? - Szybkowska, Małgorzata (Nursing in the 21st Century, 2011)
Introduction. In the last years worldwide, particularly in the highly developed countries, an increasing number caesarian sections has been performed. Caesarian section is the most common intervention in worldwide obstetrics. It is estimated that every fourth baby is borne by cesarean section. “The epidemic” of caesarian section has been observed in Poland now. A novel problem of the recent years is caesarian section on patient’s request.Aim. The increasing number of caesarian sections forces you to a more thorough recognition of the benefits as well as the negative consequences of a surgical termination of pregnancy.Results. This work presents both the benefits as well as the risks that may be associated with a caesarian section. Also presented is the ethical and legal aspect of performing a caesarian section without medical indications.Conclusions. The issue of cesarean section on demand appears to be the problem which still remains unsolved. Medical and legislative dillemas makes it the aim of further medical trials leading to establish clear guideline for gynecologists and obstetricians.